The Mechanical Performance of a Novel Self-Adhesive Restorative Material - Lohbauer, Ulrich; Belli, Renan (Journal of Adhesive Dentistry, 2020)
Purpose: The development of a novel material requires a comprehensive pre-clinical assessment of clinical longevity before any market release. This study aimed to investigate the mechanical performance of a novel self-adhesive restorative material (ASAR MP4).
CRIS-Team WoS Importer:2020-03-06